Development and application of a UPLC‐MS/MS method for simultaneous determination of fenofibric acid and berberine in rat plasma: application to the drug–drug pharmacokinetic interaction study of fenofibrate combined with berberine after oral administration in rats. (21st January 2016) - Li, Guofei; Yang, Fan; Liu, Mei; Su, Xianying; Zhao, Mingming; Zhao, Limei
Abstract: With the purpose of carrying out pharmacokinetic interaction studies ofnberberine (BBR) and fenofibrate (FBT), an UPLC‐MS/MS method has been developed and validated. The analytes, BBR and fenofibric acid (FBA, metabolite of FBT) and the internal standard, tetrahydropalmatine, were extracted with dichloromethane–diethyl ether (3:2, v / v ) and separated on an Agilent Eclipse XDB C18 column using a mobile phase composed of acetonitrile and water. With positive ion electrospray ionization, the analytes were monitored on a triple quadrupole mass spectrometer in multiple reaction monitoring mode. Linear calibration curves were obtained over the concentration ranges of 0.1–100.0 ng/mL for BBR and 10.0–50, 000.0 ng/mL for FBA. For BBR and FBA, the intra‐ and inter‐day precisions were <11.5 and 11.9%, respectively. The accuracy was within 11.7% and 11.3%. The mean recoveries of BBR at three concentrations of 0.2, 20.0, 80.0 ng/mL were >85.6%, and those of FBA at three concentrations of 20.0, 2500.0, 40, 000.0 ng/mL were >87.9%. Consequently, the proposed method was applied to the pharmacokinetic interaction study of FBT combined with BBR after oral administration in rats and was proved to be sensitive, specific and reliable to analyze BBR and FBA in biological samples simultaneously. Copyright © 2016 John Wiley & Sons, Ltd.